Decision Support System Of AMIK Medicom Promotion Strategy Determination Using AHP Method - sutrisno situmorang; Jontinus Manullang (Marqcha Institute, 2022)
Every year, both public and private universities carry out campus promotion activities to introduce and find prospective new students. In carrying out this promotion, appropriate promotional media are needed such as: brochures, banners, football/volleyball, educational exhibitions, electronic media, through radio and social media, such as Facebook and Instagram. The main priority of the promotion is getting students according to the capacity that has been provided and getting students according to the promotion target. Therefore we need the right promotional media. In decision making, the researcher uses the AHP (Analytical Hierarchy Process) method. The AHP (Analytical Hierarchy Process) method is used to determine the weight of the criteria, the working principle of AHP is to simplify a complex problem that is structured, strategic, and dynamics into their parts and organize them in a hierarchy. Then the importance of all variables is given a subjective numerical value about the relative importance of these variables compared to other variables. The results of the assessment weights are two, namely feasible and not feasible.